Verbal Extremism in Everyday Interpersonal Communication - S. V. Doronina (Теория и практика судебной экспертизы, 2019)
The extremist statements are diverse and can be classified in a range of aspects: semantic, pragmatic and rhetorical. Analysis of expert practice enables to distinguish two semantic classes: statements about national/religious group and statements about nationalist ideology. In terms of pragmatism the statements are divided into the following types: calls for action against a group; statements about actions against a group and negative attitude to it; humiliation of group members; threat to group members. Apart from that constative statements are divided into two subgroups depending on their rhetorical structure: evaluative statements and statements containing justification for negative judgments. The content and pragmatic signs of “extremist” contexts can be found in various combinations limited by the features of a communicative situation. The article summarises expert practice on the study of extremist statements uttered primarily during interpersonal domestic disputes. It is shown that the variety of statements can be reduced to a finite list of features which are a special subject of the research.